Ornamental nationalism : archaeology and antiquities in Mexico, 1876-1911 - Valiant, Seonaid (Brill's Studies on Art, Art History, and Intellectual History Ser., 2017)
"In Ornamental Nationalism: Archaeology and Antiquities in Mexico, 1876-1911, Seonaid Valiant examines the Porfirian government's reworking of Indigenous, particularly Aztec, images to create national symbols. She focuses in particular on the career of Mexico's first national archaeologist, Inspector General Leopoldo Batres. He was a controversial figure who was accused of selling artifacts and damaging sites through professional incompetence by his enemies, but who also played a crucial role in establishing Mexican control over the nation's archaeological heritage. Exploring debates between Batres and his rivals such as the anthropologists Zelia Nuttall and Marshall Saville, Valiant reveals how Porfirian politicians reinscribed the political meaning of artifacts while social scientists, both domestic and international, struggled to establish standards for Mexican archaeology that would undermine such endeavors"--